Robust Nanofiber Mats Exfoliated From Tussah Silk for Potential Biomedical Applications - Ming Chen (Frontiers Media S.A., 2021)
Nanofibers as elements for bioscaffolds are pushing the development of tissue engineering. In this study, tussah silk was mechanically disintegrated into nanofibers dispersed in aqueous solution which was cast to generate tussah silk fibroin (TSF) nanofiber mats. The effect of treatment time on the morphology, structure, and mechanical properties of nanofiber mats was examined. SEM indicated decreasing diameter of the nanofiber with shearing time, and the diameter of the nanofiber was 139.7 nm after 30 min treatment. These nanofiber mats exhibited excellent mechanical properties; the breaking strength increased from 26.31 to 72.68 MPa with the decrease of fiber diameter from 196.5 to 139.7 nm. The particulate debris was observed on protease XIV degraded nanofiber mats, and the weight loss was greater than 10% after 30 days in vitro degradation. The cell compatibility experiment confirmed adhesion and spreading of NIH-3T3 cells and enhanced cell proliferation on TSF nanofiber mats compared to that on Bombyx mori silk nanofiber mats. In conclusion, results indicate that TSF nanofiber mats prepared in this study are mechanically robust, slow biodegradable, and biocompatible materials, and have promising application in regenerative medicine.